2019
DOI: 10.3390/ijerph16142565
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dental Caries, Retained Roots, and Missing Teeth with Physical Status, Diabetes Mellitus and Hypertension in Women of the Reproductive Age

Abstract: Objectives: To investigate in women of reproductive age a possible association between particular dental diseases—dental caries, retained roots, and missing teeth—with some systemic conditions—physical status score- ASA (American Society for Anesthesiologists), diabetes mellitus, and hypertension. Methods: Dental and medical history were retrieved from the electronic files of dental patients. Statistical analysis was performed using cross tabulation with the Chi-square test to explore the significance of an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…On the other hand, the association between caries and hypertension lacks biological foundation [ 38 ] and may be explained by the consequences in the individual’s diet and nutrition caused by tooth loss. People partially or totally toothless will ingest foods that have a more favourable consistency for their consumption [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the association between caries and hypertension lacks biological foundation [ 38 ] and may be explained by the consequences in the individual’s diet and nutrition caused by tooth loss. People partially or totally toothless will ingest foods that have a more favourable consistency for their consumption [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proper control of the multiple factors affecting dental caries is important to effectively reduce its prevalence. In contrast to the extensive literature on periodontitis, only some studies have attempted to determine the correlations between dental status and various systemic diseases [ 17 , 18 ], but a clear causal relationship has not yet been established since a wide range of genetic predispositions to behavioral traits are involved as common risk factors for these diseases [ 7 ]. To our knowledge, no previous study has assessed the effects of multiple NCDs, not each disease, on dental conditions in more than 10,000 patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that missing teeth were significantly associated with the risk of arterial hypertension ( p = 0.005). Interestingly, no correlation was found between the number of teeth with caries and the risk of arterial hypertension [ 29 ]. On the other hand, in the study by Darnaud et al, which included 102,330 people in a sample of people aged ≥65 years, no significant association was found between the oral variables (teeth loss, dental plaque, tartar, gingivitis) and the risk of arterial hypertension.…”
Section: Periodontitis and The Risk Of Arterial Hypertensionmentioning
confidence: 99%